2021
DOI: 10.1186/s12969-021-00493-6
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile primary Fibromyalgia Syndrome: epidemiology, etiology, pathogenesis, clinical manifestations and diagnosis

Abstract: Juvenile primary fibromyalgia syndrome (JPFS) is a chronic, musculoskeletal pain syndrome affecting children and adolescents, most commonly adolescent girls. The syndrome has a multifactorial etiology, with altered central pain processing playing an important role. The hallmark symptom is severe, widespread musculoskeletal pain. Other symptoms include sleep and mood disturbances, headaches, stiffness, and subjective joint swelling. Physical examination can reveal multiple tender points. The diagnosis is clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 92 publications
4
27
0
2
Order By: Relevance
“… 3 In children living in a HIC, juvenile fibromyalgia syndrome was reported as 1% to 6%. 55 In this review, the prevalence of juvenile fibromyalgia syndrome was comparable to that previously reported in adults in LMICs and children in HICs, at 3% (95% CI 1–10). Unlike adults, an estimate of 20% (95% CI 16–25) was noted for multi-site paediatric chronic pain (excluding fibromyalgia).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“… 3 In children living in a HIC, juvenile fibromyalgia syndrome was reported as 1% to 6%. 55 In this review, the prevalence of juvenile fibromyalgia syndrome was comparable to that previously reported in adults in LMICs and children in HICs, at 3% (95% CI 1–10). Unlike adults, an estimate of 20% (95% CI 16–25) was noted for multi-site paediatric chronic pain (excluding fibromyalgia).…”
Section: Discussionsupporting
confidence: 81%
“…53 The Global Burden of Disease 2013 Study reported a 2% prevalence of paediatric low back and neck pain, whereas the Community Oriented Program for the Control of Rheumatic Diseases (COPCORD) estimated that MSK pain prevalence ranged from 14% to 47% in adults living in LMICs in Asia, Africa, and Central/South America, suggesting the prevalence of MSK pain in LMICs differs between paediatric and adult populations. 10,54,55 In a meta-analysis on adults in LMICs, 25% of adults reported having MSK pain. 3 In contrast, this Juvenile fibromyalgia syndrome and multi-site pain have overlapping characteristics, and both fall under the umbrella of generalized pain.…”
Section: Discussionmentioning
confidence: 99%
“…Die häufigsten Diagnosen sollen kurz dargestellt werden, da verschiedene Begrifflichkeiten verwendet werden. Die Begriffe chronischer Schmerz, Schmerzerkrankung, Schmerzsyndrom und juvenile(s) Fibromyalgie(syndrom) [9] werden häufig synonym angewendet und bedeuten Ähnliches.…”
Section: Chronische Muskuloskelettale Schmerzenunclassified
“…Up to 5% of adolescents suffer from debilitating, chronic musculoskeletal (MSK) pain1 2 affecting quality of life, school attendance, mood and family function, and posing a significant economic burden 3–14. Current treatments for chronic MSK pain are suboptimal 15.…”
Section: Introductionmentioning
confidence: 99%